Protective effects of Apelin-13 on nicotine-induced H9c2 cardiomyocyte apoptosis and oxidative stress - Can Xu; Xinyu Nie; Ru Xu; Luyang Zhou; Dongjin Wang (Tobacco Induced Diseases)
Introduction We aimed to explore the role of Apelin-13 in resisting oxidation, inflammation as well as apoptosis and its underlying mechanisms of action using a model of nicotine-induced H9c2 cardiomyocyte injury.